The Consumer’s pro environmental attitude and its impact on green purchase behavior - Sheraz, Neelam; Saleem, Saima; sultan, Shahbaz (The journal of contemporary issues in business and government, 2021)
This paper aims to analyze the consumer’s pro environmental behavior and attitude about ecological products. The aim of this study is to analyze the consumer purchase intention and ecological behavior towards the green items. In this study the researcher has thoroughly examined the consumers personal norms that how a consumer react about the environment friendly products. Governments and other companies, as significant financial institutions have started to give a guarantee towards natural assurance by changing production strategies, produce green items, and modifying ecological security arrangements. This paper analyzed the environment friendly products purchase intention is safe for an environment; the customers would have been environment concern and environmental attitude. This study has investigated the customer’s pro-environmental attitude, personal norms, social norms and less damaging the environment products purchase intention, which are less harm for the earth, impact on environment friendly product behavior. The data were collected from the 403 individuals, males and females who lived in Rawalpindi and Islamabad through survey questionnaires. The usable questionnaires were 403 as convenience sampling techniques was used which were used for the purpose of data analysis. Researcher has chosen the Cross-sectional study. The data was analyzed through SPSS in which data was measure its frequency, variance, linear regression, the descriptive statistics of the dependent and independent variables, and mediator variables with independent and dependent variables. Results indicate that relationship result the relationships of social norms with green purchase behavior, personal norms with green purchase behavior and pro-environmental attitude with green purchase behavior were found significant This study developed a deeper understanding of the impact of independent variables personal norms, social norms and pro environmental behavior of customers with the mediating effect of green purchase intention on green purchase behavior.